2000
DOI: 10.2337/diacare.23.12.1791
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and characteristics of diabetic patients with no ongoing care in South Auckland.

Abstract: OBJECTIVE: To describe the prevalence of default from diabetes care and to reveal associated characteristics among patients with known diabetes in urban South Auckland, New Zealand. RESEARCH DESIGN AND METHODS: We developed a cross-sectional household study of patients with known diabetes and compared those patients with and without ongoing care. Ongoing care was defined as having been clinically reviewed at least once in the previous 10 months. RESULTS: Of the 1,488 European, Maori, and Pacific Islander subje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
27
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 12 publications
5
27
0
Order By: Relevance
“…The authors concluded that these patients with “milder” disease may have been discharging themselves from clinic due to the belief that their disease was not severe enough to warrant intensive therapy. Simmons et al and Currie et al had similar results [13,24]. The differences between our population of defaulters and defaulters described by others likely reflect the referral pattern of our region in which the more complex patients with advanced disease are referred to tertiary care while patients with milder disease are cared for in the community.…”
Section: Discussionsupporting
confidence: 77%
“…The authors concluded that these patients with “milder” disease may have been discharging themselves from clinic due to the belief that their disease was not severe enough to warrant intensive therapy. Simmons et al and Currie et al had similar results [13,24]. The differences between our population of defaulters and defaulters described by others likely reflect the referral pattern of our region in which the more complex patients with advanced disease are referred to tertiary care while patients with milder disease are cared for in the community.…”
Section: Discussionsupporting
confidence: 77%
“…Evidence of age as a predictor of programme attrition or missed diabetes care appointments has been inconsistent in the diabetes literature with some studies reporting an association [17,21,22,28,46], while others not finding an association [10,12,15,25,26]. We found that patients younger than 45 and aged 65 years or older were more likely to drop out from recommended services.…”
Section: Discussionmentioning
confidence: 62%
“…The reasons for dropout from a diabetic care can be generally summarized into the following three categories: 1) patient-oriented problem (2,(11)(12)(13)(14)(15)(16)(17), 2) health-care provideroriented problem (11,18,19), and 3) physician-patient relationship (5,20). For the patient-oriented problem, gender, age, ethnicity, educational level, economical status, tobacco use, obesity, the duration of disorder, glycemic control, and psychological problems among others can be considered.…”
Section: Introductionmentioning
confidence: 99%